Psychological Analysis of Experiencing Psychological Well-Being - Volynets, Natalia (Psychological Prospects Journal, 2018)
The psychological analysis of the personal psychological well-being is presented in the article. The process of experiencing psychological well-being in the human consciousness and the dynamic process of creating an experience of psychological well-being or unwell-being by personality is described.The experience of psychological well-being is considered as a psychic institution that has its own structure and can be represented in human consciousness as a representative form of its own internal reflexed successful I-existence, in which person implements the process of life.It has been outlined that psychological well-being is connected with emotionally rich living of positive emotions with the feasibility of plans, actions, affairs, work and life in general, as well as with the care of the closest surrounding. The peculiarities of the personality’s experience of distress, which is connected with the emotionally rich analysis of the I-existence, with the fear of the impossibility of realizing one’s own life, isolation, which leads to anxiety, frustration, depression and mental deprivation of the individual as a mental state, is described, and occurs in situations where prolonged time is impossible and limited to the satisfaction of life needs.The experience of psychological well-being is considered as a dynamic, immanent process that is directly given and tested by the subject and subordinated to the target determination. It is noted that the substantive context of the experience of well-being reflects not the surrounding object world itself, but the subjective reflection of the inner world of meanings, behavior and activities, as well as the external world in its diversity of possibilities to satisfy the actual motives and needs of the subject.In this context, the experience of psychological well-being-unwell-being appears in the consciousness of the subject as the result of the internalization of these three worlds (semantic or behavioral (activity) worlds or the space of being) in the form of subjective contemplation of its own I-existence, which is evaluated as prosperous or disadvantaged.